Epistemic Indefinites: Are We Ignorant About Ignorance? - Alonso-Ovalle, Luis; Menéndez-Benito, Paula (Proceedings of the Amsterdam Colloquium, 2013)
Epistemic indefinites make an existential claim and convey that the speaker does not know which individual makes this claim true. The account put forward by Aloni and Port [3, 2] which we will dub the Lack of Relevant Identification Approach defends that not knowing who means that the speaker cannot identify the individual that satis es the existential claim in a contextually relevant way. The Variation Approach (see, e.g., Alonso-Ovalle and Menendez Benito [5], Chierchia [7], Falaus [9], Giannakidou and Quer [16]) assumes that not knowing who means that that individual is not the same in all of the speakers epistemic or doxastic alternatives. In this paper, we will argue that the behaviour of Spanish algun presents challenges for both approaches. Our conclusion will be that we still lack a clear understanding of what the ignorance component conveys.